Propagation of Oroxylum indicum (L.) Vent, a Vulnerable Medicinal Tree through Organogenesis (Plant Tissue Culture and Biotechnology, 2013)
Plant Tissue Cult. & Biotech. 23(1): 127?132, 2013 (June)DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15570